Vanitas - Langenskiöld, Christian (My University, 2018)
My thesis project consists of a Master’s Thesis as well as eleven photographs that were presented at Kuvan kevät in May 2018. The photographs are the result of the work I have done at the Academy of Fine Arts during my master’s studies and the purpose of the text is to give an account of how my work evolved into what became my part of the Kuvan kevät exhibition. In a broad sense my interest as an artist circles around the human condition. Especially what it is like to live as a vulnerable being and how our mortality is reflected in our inner landscape, our behaviour and how we organize ourselves in groups and societies. In my thesis it has been my aim to look at how this interest has come about and how it has shaped my work. I also speculate about the direction that it is taking me in. During the last six years I have worked with subjects such as a fallout shelter, surgery, prosthetics and hospitals and the purpose of my thesis has partly been to reflect on how these themes relate to one another in my practice. My intention has been to present the questions and ideas that interest me as an artist in order for me to develop a more defined practice.
Keywords: fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|